To find the solution to the quadratic equation 2x^2 – 5x = 6, we need to rearrange the equation in the form ax^2 + bx + c = 0, where a, b, and c are constants.
So, let's begin:
2x^2 – 5x = 6
2x^2 – 5x - 6 = 0
The equation is now in the form ax^2 + bx + c = 0, where a = 2, b = -5, c = -6.
To solve this quadratic equation, we can use the quadratic formula. The quadratic formula is given by:
x = (-b ± √(b^2 - 4ac)) / (2a)
In our case, a = 2, b = -5, and c = -6.
Let's substitute these values into the quadratic formula:
x = (-(-5) ± √((-5)^2 - 4(2)(-6))) / (2(2))
x = (5 ± √(25 + 48)) / 4
x = (5 ± √73) / 4
Now, let's round these values to the nearest hundredth:
x ≈ (5 + √73) / 4 ≈ 2.37 (rounded to the nearest hundredth)
x ≈ (5 - √73) / 4 ≈ -0.87 (rounded to the nearest hundredth)
Therefore, the solution to the quadratic equation 2x^2 – 5x = 6, rounded to the nearest hundredth, is approximately x ≈ 2.37 and x ≈ -0.87.
What is the solution to the quadratic equation 2x^2 – 5x = 6 Assume that the solution has been rounded to the nearest hundredth, if applicable.
1 answer